Comptes Rendus. Biologies 2020
DOI: 10.5802/crbiol.15
|View full text |Cite
|
Sign up to set email alerts
|

La domestication des champignons Penicillium du fromage

Abstract: Jeanne Ropars et al. having undergone bottlenecks. The different cheese populations have acquired traits beneficial for cheese making in comparison to non-cheese populations, regarding color, spore production, growth rates on cheese, salt tolerance, lipolysis, proteolysis, volatile compound or toxin production and/or competitive ability. The cheese populations also show degeneration for some unused functions such as decreased ability of sexual reproduction or of growth under harsh conditions. These recent find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 73 publications
(247 reference statements)
0
13
0
Order By: Relevance
“…This group is economically important and is typically used for the production of cheese like brie or camembert (Thom 1906 ). Taxonomically, this group and its six accepted species needs to be revised, but is complicated due to several past domestications (Ropars et al 2020a , b ). As there is little to no phylogenetic variation to guide identifications, we accept the name under which genomes from this group were submitted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This group is economically important and is typically used for the production of cheese like brie or camembert (Thom 1906 ). Taxonomically, this group and its six accepted species needs to be revised, but is complicated due to several past domestications (Ropars et al 2020a , b ). As there is little to no phylogenetic variation to guide identifications, we accept the name under which genomes from this group were submitted.…”
Section: Resultsmentioning
confidence: 99%
“…Some species are used in the production of a particular fermented food, with significant contributions to improving food safety, nutritional value, organoleptic quality and contributing to food preservation (Bourdichon et al 2012 ). Conversely, some molds are considered food contaminants causing spoilage and the production of toxic metabolites (EFSA 2023 ; Davies et al 2021 ; Rico-Munoz et al 2019 ; Avery et al 2019 ).Mold growth is often considered an undesirable characteristic of aged products, with some exceptions, such as the use of Penicillium camemberti and Penicillium roqueforti in cheeses (Ropars et al 2020a ; Hymery et al 2014 ), and Penicillium nalgiovense and Penicillium salamii on cured meats (Magistà et al 2016 ; Mintzlaff and Leistner 1972 ). Some of the microbial species naturally found on fermented foods today originated from “domestication events”.…”
Section: Introductionmentioning
confidence: 99%
“…The other cheese population, named non-Roquefort, is constituted by a single clonal lineage, due to a recent strong selection for a single “performant” strain, and is found in all types of blue cheese worldwide except Roquefort PDO cheeses. The non-Roquefort population display phenotypes more suited for industrial cheese production, such as a more efficient cheese cavity colonization ability, higher tolerance to salt, to acidic pH and to lactic acid compared to other populations (Dumas et al 2020; Ropars et al 2020; Crequer et al 2023), and the production of volatiles important for aroma and flavor, e.g. methyl ketones (Caron et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…When this study was performed, four populations had been identified in P. roqueforti, two populations being used to produce cheeses and two populations being found in molded silage and lumber or in spoiled food (Dumas et al 2020). The two populations used for cheese maturation each show footprints of bottlenecks and a domestication syndrome, with phenotypes contrasting with those of the non-cheese populations and beneficial for several important aspects of cheese safety, appearance and flavor (Dumas et al 2020;Caron et al 2020;Crequer et al 2023). The two cheese populations each correspond to a clonal lineage, with contrasted phenotypes and diversity levels, and inoculated in different types of cheeses, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…While several cheese-making fungi have been studied recently, it is important to add study cases in additional lineages, as it allows addressing the question of whether adaptation to a similar medium leads to convergent traits. In the case of cheese-making fungi, one can expect convergence for example for more or less rapid growth on cheese, higher proteolysis and lipolysis abilities, higher competitive abilities and greater production of positive volatile compounds (Ropars et al, 2020a, 2020b). Geotrichum candidum (teleomorph Galactomyces candidus ) is a dimorphic fungus (i.e., able to grow as a yeast or a mycelial form), commonly used for cheese-making, but also thriving in other environments such as soil, plants and fruits.…”
Section: Introductionmentioning
confidence: 99%